English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

If
A=y + 1/(y+3) find
dA/dy, simplyfying the answer

2007-06-18 10:19:22 · 3 answers · asked by Man of Doubts 2 in Science & Mathematics Mathematics

3 answers

Use the quotient rule!

A = (y+1)/(y+3)

[[Quotient rule: dy/dx = (u'v - uv') / v^2

u and v are the numerator and denominator of the function, respectively]]

u= y+1
u'=1

v= y+3
v'=1

dA/dy = [ (y+3) - (y +1) ] / [ (y+3)^2]
dA/dy = 2 / [ (y+3)^2 ]
dA/dy = 2 / (y^2+ 6y + 9)

That's your answer! Hope that helped!

2007-06-18 10:30:37 · answer #1 · answered by Ali M 2 · 0 0

You have two additive terms in y = A, so you differentiate term by term. The second term in a bit tricky, since it is, expressed as a numerator,
(y+3)-1. However, the power rule applies, and you have a "1" coefficient for y", so you get
dA/dy = 1 (for d(y)/dy) -1 (y+3)^-2

2007-06-18 10:26:24 · answer #2 · answered by cattbarf 7 · 0 1

dA/dy=1-1/((y+3)^2)=((y+4)*(y+2))/((y+3)^2)

2007-06-18 10:26:12 · answer #3 · answered by anechka 2 · 0 1

fedest.com, questions and answers